2009
DOI: 10.2139/ssrn.967253
|View full text |Cite
|
Sign up to set email alerts
|

An Inflated Multivariate Integer Count Hurdle Model: An Application to Bid and Ask Quote Dynamics

Abstract: In this paper we develop a model for the conditional inflated multivariate density of integer count variables with domain Z n . Our modelling framework is based on a copula approach and can be used for a broad set of applications where the primary characteristics of the data are: (i) discrete domain, (ii) the tendency to cluster at certain outcome values and (iii) contemporaneous dependence. These kind of properties can be found for high or ultra-high frequent data describing the trading process on financial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…The copula approach for constructing joint distributions has gained popularity in recent years in applied econometric studies, including models with discrete outcomes (Van Ophen (1999) [1]; Cameron et al (2004) [2]; Zimmer and Trivedi (2006) [3]; Bien et al (2011) [4]; Winkelmann (2012) [5]). While copula researchers have long understood that a multivariate discrete distribution does not possess a unique copula representation (Marshall (1996) [6]), recent research also indicates that any copula applied to discrete data is not identified.…”
Section: Introductionmentioning
confidence: 99%
“…The copula approach for constructing joint distributions has gained popularity in recent years in applied econometric studies, including models with discrete outcomes (Van Ophen (1999) [1]; Cameron et al (2004) [2]; Zimmer and Trivedi (2006) [3]; Bien et al (2011) [4]; Winkelmann (2012) [5]). While copula researchers have long understood that a multivariate discrete distribution does not possess a unique copula representation (Marshall (1996) [6]), recent research also indicates that any copula applied to discrete data is not identified.…”
Section: Introductionmentioning
confidence: 99%
“…Nonnegative integer‐valued count process models are widely used in domains such as marketing (Böckenholt, 1998), economics (Blundell, Griffith, & Van Reenen, 1999; Brännäs & Hellström, 2001; Harris & McCabe, 2019), finance (Bien, Nolte, & Pohlmeier, 2011; Heinen & Rengifo, 2007; Kirchner, 2017), and insurance (Gouriéroux & Jasiak, 2004). The benchmark model, introduced by McKenzie (1985) and Al‐Osh and Alzaid (1987) in the first‐order case (called INAR(1)) postulates that: Xt=αXt1+ϵt,t, where the thinning operator is defined as follows: conditionally on X t −1 , variable α∘ X t −1 has the distribution (Xt1,α), that is the binomial distribution with probability parameter α and size parameter X t −1 .…”
Section: Introductionmentioning
confidence: 99%